Anorexia nervosa in the family: a sibling's perspective - Withers, A.; Mullan, Barbara; Madden, S.; Kohn, M.; Clarke, S.; Thornton, C.; Rhodes, P.; Touyz, S. (Routlege, 2014)
Purpose: There is growing evidence that siblings have a role to play in the recovery from adolescent anorexia nervosa (AN), yet we know very little about the effect that AN has on them and what they do to cope. This study aims to investigate the impact of AN on adolescent siblings. Method: Semi-structured interviews were conducted with 20 adolescent siblings of young people being treated for AN, and analysed using thematic analysis. Results: The results indicate that the effects of AN on the sibling relationship can be variable, with older siblings with a pre-existing close relationship with the patient faring the best. Siblings described a number of factors that supported coping, including knowing more about the illness, the need for regular ‘time-out’ from stressful events and interactions and close supportive relationships with family members. Involvement in family-based treatment appeared to improve understanding of AN and enhanced communication within the family. Problems with family-based therapy (FBT) were discussed. Conclusion: Addressing the needs of well siblings has the potential to improve outcomes for them and their sibling with AN. FBT goes some way towards doing this, but addressing difficulties that siblings experienced could lead to further improvements in treatment.